水圧駆動腹腔内組立式ハンドの開発: (水圧駆動の利点検証) - MIYAMOTO, Hiroyuki; TAKAYAMA, Toshio; OMATA, Toru; KOJIMA, Kazuyuki; TAKASE, Kozo; TANAKA, Naofumi (Transaction of the Japan Fluid Power System Society, 2011)
In laparoscopic surgery, retracting internal organs is required for appropriate visibility and workspace. It is desired that retracting instruments be less invasive and conform better to organ surfaces. An assemblable three-fingered retractor-hand was previously developed. It had three active joints driven with wires. In this research, a new assemblable three-fingered hand is developed. The fingers of this hand are equipped with hydraulic driven bending joints, which enables simplification of the mechanism and safe retraction. There are advantages of using a hydraulic drive system such as; easier power transmission and therefore higher transmission rate. Fingertip forces are equalized and can be estimated with the help of a water pressure gauge. In addition, the load torque, at which the fingers are extended, can be adjusted by modifying precompression. Also, the hydraulic joints provide adjustable compliance because of the elasticity of the tubes in the flow path. Those benefits are verified by experiments, and an in vivo experiment is conducted.